An appraisal of the competencies of teachers of English in the Public Elementary Schools of San Juan, Batangas during the academic year, 1964-1965 - Nobles, Arsenio F. 1914- ([Quezon City s.n.], 1967)
The main objective of the study is to describe teachers of English in the municipality of San Juan in terms of educational and professional qualifications and competencies in teaching the language. It also endeavors to discover the attitudes of these teachers towards the use and teaching of English.
Thesis (M.Ed.)--University of the Philippines
Keywords: Teachers